2015
DOI: 10.1016/j.ijthermalsci.2015.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of a closed loop flat plate pulsating heat pipe under a varying gravity force

Abstract: This paper reports on an experimental study of a closed loop Flat Plate Pulsating Heat Pipe (FPPHP) tested on ground and on board of an aircraft during the 60th ESA parabolic flight campaign, during which hyper- and microgravity conditions were reproduced. The tested FPPHP consists of two brazed copper plates, into one of which a continuous rectangular channel (1.6 x 1.7 mm(2)) with 12 bends in the evaporator is machined. The channel is filled with FC-72 as working fluid with a volumetric filling ratio of 50%.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(23 citation statements)
references
References 17 publications
1
18
0
2
Order By: Relevance
“…Such passive thermal device is actually a hybrid system, since it works as a Multi-Evaporator Loop Thermosyphon (MELT) on ground [24] and as a capillary PHP in microgravity conditions. Other successful attempts were also performed by Ayel et al [25,26] in hyper/micro gravity conditions by means of parabolic flights. Their Flat Plate Pulsating Heat Pipe was filled up with FC-72, and the hydraulic diameter was 2 mm, which is higher than the capillary static and dynamic thresholds (Table 2).…”
mentioning
confidence: 99%
“…Such passive thermal device is actually a hybrid system, since it works as a Multi-Evaporator Loop Thermosyphon (MELT) on ground [24] and as a capillary PHP in microgravity conditions. Other successful attempts were also performed by Ayel et al [25,26] in hyper/micro gravity conditions by means of parabolic flights. Their Flat Plate Pulsating Heat Pipe was filled up with FC-72, and the hydraulic diameter was 2 mm, which is higher than the capillary static and dynamic thresholds (Table 2).…”
mentioning
confidence: 99%
“…16 Tubes fabricated from copper lead to high heat transport rates with minimal temperature gradients due to the high thermal conductivity of the material. 17 In this work, we therefore employed a 24 channel flat plate OHP design (1.6 Â 2.0) mm 2 (Equation (1)) and (Equation (2)) with 12 U-turns machined into a 2 mm thick copper base plate (20 Â 12) cm 2 ( Figure 4).…”
Section: Methodsmentioning
confidence: 99%
“…The critical limit of the internal diameter capable to maintain the characteristic slug/plug regime in microgravity conditions is still unknown. In addition for pulsating heat pipes tested under microgravity conditions, an intermittent thermofluid behavior has been observed by [13], as well as temperature fluctuations [12], whose origin ACCEPTED MANUSCRIPT ACCEPTED MANUSCRIPT 5 could be assigned to stop-and-start flow motions occurring inside the PHP during those phases.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…This point will be further discussed in the next section for the present FPPHP. However, if it has been demonstrated that capillary pulsating heat pipes can operate under microgravity conditions [8][9][10][11][12], and more recent studies from Mangini et al [13,14] showed that the flow pattern ACCEPTED MANUSCRIPT ACCEPTED MANUSCRIPT 4 switched from stratified flow under normal or hyper gravity conditions to slug flow under microgravity conditions, for uniform heating patterns [13] as well as non-uniform heating patterns [14]. They tested a 3 mm internal diameter tubular PHP (well above the critical diameter value fixed at around 1.66 mm for the tested fluid, FC72, at 20°C) with a transparent tube portion on the upper part of the bench above the condenser zone.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%